Reduced serum cholinesterase activity indicates splenic modulation of the sterile inflammation - Živković, Aleksandar; Tourelle, Kevin M.; Brenner, Thorsten; Weigand, Markus A.; Hofer, Stefan; Schmidt, Karsten (Journal of surgical research, 2017)
Background - Sterile inflammation is an immediate and well-coordinated immune response to surgical injury. The cholinergic system plays a pivotal role in the inflammatory response. Induced inflammation stimulates the vagus nerve, which in turn activates anti-inflammatory nonneuronal processes. Serum cholinesterase (butyrylcholinesterase [BChE]) is an enzyme that hydrolyzes acetylcholine. Measuring the activity of the BChE in blood might indicate the level of the nonneuronal cholinergic activity. The spleen is a major organ of the immune system playing an important role during inflammation. A functional connection of the neuroimmune reflex has thus far been described only in experimental settings. - Materials and methods - In 48 patients receiving major pancreatic surgery, BChE activity was measured by applying point-of-care-testing, in addition to standard laboratory tests. - Results - The BChE activity decreased in patients receiving surgery. This reduction emerged much earlier than changes in C-reactive protein concentration, an inflammatory biomarker broadly used in the clinical environment. A milder reduction in the BChE activity was observed in patients subjected to surgery with splenectomy than in those with a preserved spleen. - Conclusions - The use of the point-of-care-testing system for quick bedside diagnostics and the rapid effects of inflammation on BChE levels provide a method and a marker to facilitate the early detection of systemic inflammation. Furthermore, this study provides evidence that the experimentally documented neuroimmune interaction is part of the physiological response to surgery-induced sterile inflammation. Splenic function plays an essential role in modulating the cholinergic anti-inflammatory response.